The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s41256-021-00210-6
|View full text |Cite|
|
Sign up to set email alerts
|

Morbidity and mortality outcomes of COVID-19 patients with and without hypertension in Lagos, Nigeria: a retrospective cohort study

Abstract: Background The current pandemic of coronavirus disease (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown epidemiological and clinical characteristics that appear worsened in hypertensive patients. The morbidity and mortality of the disease among hypertensive patients in Africa have yet to be well described. Methods In this retrospective cohort study all confirmed COVID-19 adult patients (≥18 years of ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
2
21
0
2
Order By: Relevance
“…Similar findings have been reported in studies where the COVID-19-related mortality is reported to be associated with comorbid health conditions. 24,25 Although our participants working in the wards/ICUs rated these places as high-risk workplaces, the literature showed that working in the intensive care unit was not associated with increased risk of infection possibly due to protection afforded by high levels of PPEs and a decrease in infectivity that occurs in the later stages of illness although among critically ill patients. 26,27 To the best of our knowledge, this study about the perceptions of HCPs and particularly doctors in Pakistan about risks and deaths associated with COVID-19 is the first survey conducted in Pakistan.…”
Section: Discussionmentioning
confidence: 83%
“…Similar findings have been reported in studies where the COVID-19-related mortality is reported to be associated with comorbid health conditions. 24,25 Although our participants working in the wards/ICUs rated these places as high-risk workplaces, the literature showed that working in the intensive care unit was not associated with increased risk of infection possibly due to protection afforded by high levels of PPEs and a decrease in infectivity that occurs in the later stages of illness although among critically ill patients. 26,27 To the best of our knowledge, this study about the perceptions of HCPs and particularly doctors in Pakistan about risks and deaths associated with COVID-19 is the first survey conducted in Pakistan.…”
Section: Discussionmentioning
confidence: 83%
“…Four studies found preexisting CVD was associated with higher COVID-19 mortality, including 2 high-quality studies using databases from South Africa to pool together large samples. 10,11,31,32 In a national hospital registry across South Africa with 219 265 COVID-19 patients, 39% had hypertension and 23% died. 32 Both hypertension and CVD were associated with a higher adjusted odds of COVID-19 mortality (hypertension: aOR, 1.1 [95% CI, 1.0-1.1]; CVD: aOR, 2.2 [95% CI, 2.1-2.3]) after adjusting for age, race, diabetes, chronic cardiac disease, chronic renal disease, malignancy, tuberculosis, HIV, admission month, health sector, and province.…”
Section: Covid-19 Mortalitymentioning
confidence: 99%
“…The largest and highest quality evidence from SSA indicates a strong association between preexisting hypertension and CVD and COVID-19 severity and death. 10,11,31,32 Studies on preexisting hypertension or CVD on emerging viral infections showed that hypertension and CVD increased the chance of severe COVID-19 (RR, 2.5) in studies on the individual level but no association on the country level in ecological studies, perhaps because average country summary measures are often inaccurate in SSA. The association between hypertension or CVD on COVID-19 mortality was more thoroughly explored, with higher odds and RRs for CVD (2.2-6.6) than for hypertension (1.1-2.3) after multivariable adjustment in South Africa, Nigeria, Burkina Faso, and Guinea.…”
Section: Lessons From Existing Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing 2019 coronavirus disease (COVID- 19) pandemic results from infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). At the time of undertaking this review, the global burden of COVID-19 exceeded 225 million (about 2.9% of the world population) [1].…”
Section: Introductionmentioning
confidence: 99%